Comparative Bacteriostatic and Bactericidal Activities of Cefodizime against Borrelia burgdorferi Sensu Lato - Murgia, Rossella (American Society for Microbiology, 1999)
The MIC and MSC (minimum spirocheticidal concentration) and killing rate for Borrelia burgdorferi, the etiological agent of Lyme disease, were assessed for cefodizime in comparison with ceftriaxone, minocycline, azithromycin, roxithromycin, and ciprofloxacin. The range of cefodizime MICs was greater than those of azithromycin and roxithromycin but comparable to those of ceftriaxone and minocycline. The MSCs were 1 to 2 dilutions higher than the MICs of all of the tested compounds. The killing curves of cefodizime and ceftriaxone showed parallel courses. In conclusion, cefodizime exerted an activity comparable to that of ceftriaxone against B. burgdorferi.